SI BUDUR: INDONESIAN CULTURAL TOURISM FOR DIGITAL NATIVES GENERATIONS - Muhammad Rauuf Oktavian Nur; Boris Ramadhika (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
COVID-19 outbreak has affected people's activities in Indonesia. At least people in 34 provinces should stay at home to reduce this pandemic spread. This world pandemic has a massive impact on national and international travel, gatherings, and tourism activities. This research is discussing about Si Budur application that has a new concept to bring back the cultural tourism for digital natives’ generations. Especially, in this pandemic condition, the digital natives’ generations need the appropriate media to learn about their own culture. Many cultural tourism is contain important cultural value for the digital natives’ generation. This paper is talking about the use of SI BUDUR application in order to give Indonesian cultural tourism holding a chance to use a new platform in their activities, especially to counteract the COVID-19 pandemic. This research uses a descriptive qualitative method to discuss the assumption, supporting theory, and previous research. Collecting the data from previous literature and research that talking about using the digital media to bring back the cultural tourism. Researchers analyze the data by compiling the result of some previous literatures and research then comparing with the Si Budur concept. The result is interesting which shows there are many factors that will affect the implementation of Si Budur. It is an appropriate media for the digital natives’ generation to learn and get the knowledge about cultural history around them during this Covid-19 pandemic. This concept is first and fresh concept that has goals to bring back the cultural value to the digital natives’ generations. The other literatures and previous research did not have same and specific concept like Si Budur. It is offer the combination of latest technology with the amazing cultural value. Indonesia has a lot of cultural value that should be keep in touch with the digital natives’ generations. Digital natives’ generations as the main and massive generations in this era will give necessary effect to the cultural value.Keywords: COVID-19, culture, tourism, SI BUDUR